Rancang Bangun Tampilan UI untuk Game Smartphone Healthy Laifu Menggunakan Prinsip Gestalt - Arfiando Karson Eugena Lengkong; Hamdan Arfandy; Baizul Zaman (KHARISMA Tech, 2021)
Making a UI design for the Android-based Healthy Laifu application, which in making this application begins with the design of this user interface design, which is expected to increase the attractiveness of the application and make it easier for users to use the application. There are 2 designs that are made with differences in the choice of colors used, in which the color selection is done by following the theory and psychology of color and applying the Gestalt Principle concepts.